Impact of Oil Price Shocks on Sectoral Returns in Nigeria Stock Market - Onyeke, Chibueze E.; Nwakoby, Ifeoma; Onwumere, Josaphat U. J.; Ihegboro, Ifeoma; Nnamani, Chidiebere (International Journal of Energy Economics and Policy, 2020)
This paper investigates the impact of oil price shocks on stock returns in Nigeria using monthly data on four sectoral indices – Banking, Insurance, Food, Beverages, & Tobacco (FB&T) and Oil & Gas (O&G) – over the period January 2010 to December 2018. The oil price shocks are decomposed into precautionary demand, aggregate demand, and supply sources. The outcome of the estimation of a Structural Vector Autoregressive (SVAR) model suggests that precautionary demand oil shock had negative and significant impact on the sectoral returns except for FB&T whose response was insignificant; aggregate demand oil shock had a negative but insignificant impact on the sectoral returns but for the O&G sector whose response was positive although insignificant; whereas oil supply shock had a positive but insignificant impact on the sectoral returns in the Nigerian stock market. However, O&G sector was the only exception with negative response to oil supply shock, albeit, insignificantly. Keywords: Oil Price, Stock Returns, Structural VAR. JEL Classification: G DOI: https://doi.org/10.32479/ijeep.10189